Intestinal microbiome dysbiosis in alcohol-dependent patients and its effect on rat behaviors - Chuansheng Wang; Junli Yan; Keda Du; Shuai Liu; Jiali Wang; Qi Wang; Huajie Zhao; Min Li; Dong Yan; Ruiling Zhang; Fan Yang (mBio, 2023)
ABSTRACTAlcohol dependence (AD) is a worldwide epidemic of psychiatric disorders. Gut microbiota dysbiosis may be involved in the development of AD. Recently, the number of studies on the relationship between gut microbiota and alcohol is increasing. However, most previous studies were focused on rodent models and gut microbiota, and the data about the alteration of the gut fungi in AD patients were scarce. Convincing evidence of the gut microbiota’s role in the development of AD is lacking. Here, we investigated the characteristics of gut microbiota (bacterial) and mycobiota (fungal) dysbioses in AD patients and assessed the role of the gut microbiome on the behaviors of rats by fecal microbiota transfer, trying to illuminate the possible microbiota mechanism in AD development. We found that AD patients developed gut microbiota dysbiosis, displayed by the fact that the bacterial genus of Ruminococcaceae significantly decreased and that of Lachnospiraceae increased and the fungal genus of Saccharomyces and Kurtzmaniella obviously increased and that of Candida decreased. Alcohol consumption disturbs the gut equilibrium between bacteria and fungi. The fungal-to-bacterial species ratio was significantly decreased, and the bacterial-fungal trans-kingdom interactions were reduced. By transplanting the gut microbiota from AD patients to rats, we confirmed that the microbiota from AD patients induced the behavioral alterations associated with alcohol dependence in rats, including increased anxiety- and depression-like behaviors, reduced exploratory and recognition memory, and higher alcohol preference. Meanwhile, the microbiota from the AD patient donor upregulated the expression levels of cholecystokinin receptors in the frontal lobe, hippocampus, and cortex in rats, which might be involved in the development of alcohol dependence. Our results demonstrate that AD patients developed gut bacterial and fungal microbiota dysbioses and the gut microbiota may be involved in the development of alcohol addiction by regulating the endogenous cholecystokinin and related receptors’ expression. Our data open new avenues for adjuvant treating AD patients via administrating the intestinal microbiota.IMPORTANCEIntestinal microbiome dysbiosis is associated with psychiatric disease through the “microbiota-gut-brain” axis. Here, we revealed that there was obvious intestinal microbiome (including bacterial and fungal) dysbiosis in alcohol-dependent patients. Alcohol consumption seriously disturbs the gut equilibrium between bacteria and fungi, reduces the interactions among bacterial-fungal trans-kingdom, and increases intestinal permeability. Gut microbiota should be considered as a whole to study the development of alcohol dependence. The gut microbiome of alcohol-dependent patients increased the anxiety- and depression-like behavior in rats. The gut microbiota dysbiosis may promote the development of alcohol dependence by regulating the endogenous cholecystokinin (CCK) and related receptors. Hence, regulating the balance of gut microbiota and the endogenous CCK may be a potential strategy for reducing the risk of relapse in alcohol addiction patients.